Batch mode treatment of wastewater from the Maroua artisanal tannery using silica extracted from rice husks and silica/sand mixture - Jean Marie Dangwang Dikdim; Germain Vaimata Djinsi; Cornelius Tsamo (Program studi Teknik Kimia UNS, 2022)
ABSTRACT. Tanning activity consumes high volumes of water resulting in large volumes of highly colored polluted wastewater being discharged to the environment. In this study, the discoloration of the wastewater of the local artisanal tannery using SiO2 synthesized from rice husks and silica/sand mixture at different process conditions was investigated. The results revealed that the discoloration process is favorable for both adsorbents at 35oC with maximum of 61% for sand/SiO2 mixture system and 64% for SiO2 system. The presence of NaCl electrolyte enhanced the discoloration for both adsorbents increasing from 44% for sand/SiO2 mixture at 0 NaCl to 72% at 0.5M NaCl and from 49% for SiO2 system at 0 NaCl to 63 % at 0.5M NaCl. Increasing the amount of sand from 0.2 to 1 g at fixed SiO2 of 0.1 g in sand/SiO2 mixture showed discoloration from 40-41 % while increasing SiO2 in SiO2 alone system from 0.05 to 0.5 g had a discoloration of 45-71%. Results of this study shows that sand a very abundant local and worldwide material can be complemented with silica in a very low cost tannery wastewater discoloration process.Keywords: Tannery, Wastewater, Silica, Sand, Discoloration